Film programming : curating for cinemas, festivals, archives - Bosma, Peter (Wallflower Press, an imprint of Columbia University Press, 2015)
"This book explores artistic choices in the field of cinema exhibition, focusing on film theatres, film festivals, and film archives, setting the various issues of film curating in their international context. The availability of artistic and commercial film has increased overwhelmingly as a result of the digitization of the infrastructure of distribution and exhibition; in this overflow of supply a reasoned and well-grounded selection is necessary more than ever. The conventional structures of the film trade are in a process of transformation and, in the digital age, supply and demand can meet without the intervention of traditional gatekeepers; everybody can be a film curator, in a passive or active way. This volume addresses three kinds of readers: those who want to become film curators themselves, or do research of the phenomenon of film curating, and those who are critical cinema visitors who want to investigate the story behind the process of selection of the available film supply and the way to present these films"- Resumé vydavatel
Keywords: filmové festivaly a přehlídky; filmové archivy; kina; film festivals; film archives; motion picture theaters; filmové kurátorství; elektronické knihy; studie; electronic books; studies